2020
DOI: 10.2147/ott.s266649
|View full text |Cite
|
Sign up to set email alerts
|

<p>Structural and Functional Overview of TEAD4 in Cancer Biology</p>

Abstract: TEA domain transcription factor 4 (TEAD4) is an important member of the TEAD family. As a downstream effector of the Hippo pathway, TEAD4 has essential roles in cell proliferation, cell survival, tissue regeneration, and stem cell maintenance. TEAD4 contains a TEA DNA binding domain that binds the promoters of target genes and a Yesassociated protein/transcriptional co-activator with PDZ-binding motif (YAP/TAZ) binding domain that associates with transcriptional cofactors. TEAD4 coordinates with YAP, TAZ, VGLL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 88 publications
(147 reference statements)
1
27
0
Order By: Relevance
“…YAP and TAZ are transcriptional co-activators that shuttle between the cytoplasm and the nucleus. They recognize homologous cisregulatory elements by interacting with other transcription factors such as TEA domain family members, which are involved in cell proliferation, tissue regeneration, and stem cell maintenance (Piccolo et al, 2014;Chen M. et al, 2020). The continuous activation of this system can promote abnormal cell proliferation (Koo and Guan, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…YAP and TAZ are transcriptional co-activators that shuttle between the cytoplasm and the nucleus. They recognize homologous cisregulatory elements by interacting with other transcription factors such as TEA domain family members, which are involved in cell proliferation, tissue regeneration, and stem cell maintenance (Piccolo et al, 2014;Chen M. et al, 2020). The continuous activation of this system can promote abnormal cell proliferation (Koo and Guan, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…RTEF-1 is highly expressed in skeletal muscle; initial studies focused on its role in blastocyst formation and reported that TEAD4 is required for specification of the trophectoderm lineage in preimplantation embryos [ 7 , 8 ]. Recently, RTEF-1 was demonstrated to be a novel prognostic marker of gastric cancer, breast cancer, colorectal cancer, melanoma, laryngeal cancer, and head-neck squamous cell carcinoma [ 6 , 9 ]. Apart from its oncogenic role in the canonical Hippo-YAP/TAZ pathway, other studies have reported its participation in many pathological process of cardiovascular disorders, such as increasing endothelial-dependent microvascular relaxation [ 10 ], improving glucose clearance and insulin sensitivity in the endothelium [ 11 ], and stimulating cardiac hypertrophy in the myocardium [ 12 ], as well as accelerating recovery from ischemia [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…TEAD4 always coordinates with YAP/TAZ to regulate gene transcription when Hippo signaling inactivates 20 . TEAD4 was highly expressed in several cancers, which indicated it may be a novel prognostic marker 31 . Interestingly, we found that TEAD4 was overexpressed in ESCC tissues from TCGA and there was a positive correlation between TEAD4 and KIF4A ( r = 0.355, p < 0.001, Figure 6A,B).…”
Section: Resultsmentioning
confidence: 82%
“…Actually, this is closely related to YAP gene amplification or mutations of the inhibitory factors 27,28 . TEAD4, a downstream transcription factor of Hippo/YAP signaling, is overexpressed in several cancers and associated with tumor progression 29–31 . Among the members of TEAD family, TEAD4 is known as a driven gene and involved in the development of ESCC 32,33 .…”
Section: Introductionmentioning
confidence: 99%